Synthesis, Characterization and Antitumor Efficacy of Silver Nanoparticle from Agaricus bisporus Pileus, Basidiomycota - OWAID, Mustafa Nadhim; NAEEM, Ghassan Adnan; MUSLIM, Rasim Farraj; OLEIWI, Raheel Saeed (Walailak Journal of Science and Technology (WJST), 2018)
The object of this study is to synthesize and characterize silver nanoparticles from Agaricus bisporus pileus extracts and their applications. Agaricus bisporus-mediated synthesis of AgNPs was characterized using changing the color solution, UV-Visible spectroscopy, SEM, AFM, SPM, FTIR spectrum, XRD, and EDS analyses. The change of the mixture color of 10-3 M AgNO3 with the watery extract of fresh A. bisporus caps from colorless to brown color is an indicator for the formation of silver nanoparticles (AgNPs). The UV-Visible spectrum exhibits the absorption peak at 418 nm. The FTIR spectra exhibited that the structures of amino acids, polysaccharides, and polyphenols in the crude extract of A. bisporus are not affected because of the joining and interaction of their functional groups with silver ions, and act as reducing and capping agents to the biosynthesized Ag nanoparticles. SEM and EDS refer to the formation of AgNPs with irregular or spherical shapes. The XRD pattern exhibits face-centered cubic (fcc) silver nanocrystals, with crystalline AgNPs size of 43.9 nm. The biosynthesized AgNPs play a suitable role against mouse cell line, which has receptors for polioviruses (L20B). After exposure of the colloid AgNPs to UV radiation (256 nm), the absorption band transferred from 418 nm to 435 nm, indicating that UV rays affect on physical properties of AgNPs. Roughness average of the biosynthesized AgNPs from A. bisporus caps is 15.4 nm, but the roughness is increased after UV irradiation for 1 h to average 33.6 nm. Histograms of particle size distribution of AgNPs show the average of AgNPs is 103.57 nm, while the size of nanoparticles reaches 69.47 nm after exposure to UV radiation of 256 nm. The use of UV radiation leads to enhanced characteristics of silver nanoparticles.